Critical Pedagogy in Uncertain Times
XIV, 226 p.
Keywords: This book brings together the most important figures in the evolution of Critical Pedagogy to provide comprehensive analyses of issues related to the struggle against the forces of neoliberalism and the imperial-induced privatization, not just in education, but in all of social life through the radical democratizing forces of critical pedagogy.